URGENSI PENGGUNAAN SANKSI HUKUM PIDANA DALAM KONTEKS PENANGGULANGAN KEJAHATAN - Pratiwi Ayu Daulat (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2017)
The use of criminal sanctions concerning policy issues and is a necessity for use in managing and controlling crime. Thus irrational if efforts to eliminate crime that is based on the grounds that the criminal was in retaliation, because the purpose of a criminal one prevention to achieve the welfare of society. As one means of law enforcement policy in order to control crime, the use of sanctions (law) criminal is not an absolute. If used, then the problem is the policy should be rational use with due regard to the approach of humanistic and social interests that contain certain values which need to be protected. As a criminal policy that extreme attitude to abolish sanctions (law) does not constitute a criminal policy measures. For what needs to be done in the policy to make efforts to control and crime prevention is an integrated approach between penal policy and nonpenal.